Evaluation of Maxillofacial Characteristics in Individuals with Anterior Open Bite Using Denture Frame Analysis - Emre Cesur; Ayşegül Köklü (Galenos Yayinevi, 2020)
Keywords:The aim of this study was to evaluate the effectiveness of denture frame analysis (DFA) in individuals with anterior open bite who had completed pubertal peak growth (post-peak).Methods:This retrospective study was conducted using the cephalometric radiographs and hand-wrist X-rays of 50 individuals with open bite (mean age: 17.33±3 years; 35 female, 15 male) and a control group of 50 individuals without open bite (mean age: 17.38±2.72; 35 female, 15 male). All individuals included in the study were skeletal Class I and had completed or nearly completed skeletal growth. Skeletal and dental measurements pertaining to DFA were done and the data were analyzed using independent samples t test and Mann-Whitney U test.Results:Measurements assessing the vertical dimension showed that GoGn/SN, Frankfurt horizontal (FH)/mandibular plane (MP), palatal plane (PP)/MP, occlusal plane (OP)/MP, and OP-MP/PP-MP measurements were significantly greater in the open bite group (p<0.001). AB/MP angle was significantly larger in the control group (p<0.05). The open bite group had shorter A'-P' (posterior maxillary length; p<0.05) and, therefore, higher A'-6'/A'-P' ratio (p<0.01).Conclusion:Our results suggest that there may be a close association between maxillary OP inclination and mandibular position in individuals with open bite, and that open bite may arise due to maxillary denture base deficiency, especially in the posterior region. DFA may be useful in the differential diagnosis of open bite and in treatment planning, particularly when determining the need for tooth extraction.